Քիմիաթերապիայի և թիրախային բուժման դերը կոլոռեկտալ քաղցկեղով հիվանդների մոտ - Ս. Գ. Բարդախչյան (Հայաստանի ԳԱԱ)
Колоректальный рак (КРР) является одним из самых распространенных раков в мире и одним из первых причин раковой смертности. За последние десятилетия выживаемость больных с КРР значительно увеличилась.Colorectal cancer (CRC) is one of the most widespread cancers in the world and one of the leading causes of cancer death. For the last decades survival with CRC patients is substantially improved.
Keywords: Internal medicine; Neoplasms; Tumors; Oncology (including Cancer)